2018
DOI: 10.1001/jamaoto.2018.0667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Budesonide Added to Large-Volume, Low-pressure Saline Sinus Irrigation for Chronic Rhinosinusitis

Abstract: ClinicalTrials.gov Identifier: NCT02696850.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 31 publications
2
81
0
Order By: Relevance
“…Although the questionnaire may be a good resource for evaluating QOL in CF patients, it has not been validated for this purpose . As alluded to in the opening paragraph of the discussion, baseline SNOT‐20 scores in this cohort of patients are much lower than what is typically observed in standard CRS patients, in which average baseline SNOT‐22 scores are generally greater than 40 . This, in addition to the lack of a validated questionnaire to specifically target sinonasal QOL in the CF population, makes assessment of this patient population difficult, and highlights the importance of development of a sinus‐specific QOL instrument for use in the CF population.…”
Section: Discussionmentioning
confidence: 93%
“…Although the questionnaire may be a good resource for evaluating QOL in CF patients, it has not been validated for this purpose . As alluded to in the opening paragraph of the discussion, baseline SNOT‐20 scores in this cohort of patients are much lower than what is typically observed in standard CRS patients, in which average baseline SNOT‐22 scores are generally greater than 40 . This, in addition to the lack of a validated questionnaire to specifically target sinonasal QOL in the CF population, makes assessment of this patient population difficult, and highlights the importance of development of a sinus‐specific QOL instrument for use in the CF population.…”
Section: Discussionmentioning
confidence: 93%
“…Tait et al also performed a double‐blinded, placebo‐controlled trial comparing budesonide irrigations vs saline irrigations in 61 patients. All patients used a 240‐mL irrigation once daily and were evaluated after 30 days by the SNOT‐22, LK grading, and a modified Clinical Global Impressions scale.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies, however, consisted of either completely nonsurgical cohorts, or ones in which surgical extent was inconsistently described. In particular, Tait et al found that patients who did not undergo surgery fared better than those who did have surgery. Although the difference did not reach statistical significance, it does highlight the question of whether all sinus surgery is equal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations